Diplomasi Internasional dalam Penyelesaian Sengketa Keamanan Maritim: Studi Hubungan Indonesia – Singapura dalam Kasus Selat Malaka - Buana, Resky Septi; Ilmih, Andi Aina (Law, Development and Justice Review, 2025)
The aim of this research is to analyze the role of international diplomacy, particularly maritime and legal diplomacy, in maintaining maritime security and resolving boundary disputes in the Strait of Malacca between Indonesia and Singapore. The Strait of Malacca is a strategic global trade route vulnerable to threats such as piracy, terrorism, and territorial violations. This study employs a normative legal method with a conceptual and statutory approach, drawing from both national and international regulations. The urgency of this research lies in the need for effective regional collaboration and legal enforcement to maintain stability amid increasingly complex maritime threats. The findings indicate that maritime and legal diplomacy play crucial roles in fostering cross-border cooperation, strengthening maritime monitoring systems such as IMSS and VTIS, and resolving maritime boundaries based on the principles of the 1982 UNCLOS and bilateral agreements. Peaceful dispute resolution through legal diplomacy enhances Indonesia’s position in safeguarding sovereignty and establishing maritime legal order. Thus, international diplomacy proves to be a strategic instrument in achieving sustainable maritime security and regional stability in the Strait of Malacca.